ANALISIS POTENSI PERTANIAN TANAMAN JAGUNG DESA PADENGO KECAMATAN DENGILO BERBASIS SISTEM INFORMASI GEOGRAFI (SIG) - Hasan, Hais; Kurniawati, Nevi; Ramadhani, Bulan Suci; Lodjo, Liberty (LEMBAGA KAJIAN PEMBANGUNAN PERTANIAN DAN LINGKUNGAN (LKPPL), 2025)
Geographic information system (GIS) is a technology that is currently a very important tool in storing, manipulating, analyzing and displaying natural conditions with the help of attribute data and spatial data that can be visualized. The purpose of this study is: To determine the potential suitability of agricultural land based on Geographic Information System (GIS) Method: used in this study is a qualitative approach method. Results: this study is land suitability using ArcGIS 10.3 software, there are 31.65 ha for land not suitable for corn commodities and 228.94 ha are classified as